EXPRESSION STUDY OF BLOOD DISEASE RESISTANCE GENE IN BANANA (Musa spp.) - Rizky Rahmawati NIM : 20616003, Aisha
Blood disease is one of the serious banana diseases caused by Blood Disease Bacterium (BDB) which cause huge loss of its production in Indonesia. Genetic basis information of plant defense mechanism on blood disease in ethylene pathway is not available. The knowledge of transcriptomic and genes expression profile will give important information on plant response to BDB infection. In this study, two different banana cultivars with different genomes, Musa acuminata cv. Mas Kirana (AA group) and Musa balbisiana cv. Klutuk (BB group) were observed in transcriptomics scope. RNA-seq analysis generated 15-19 million total reads. Approximately, 31679 genes were expressed and 56 genes were assigned to plant-pathogen interactions in ethylene pathway for M.acuminata whereas M. balbisiana had 28890 genes were expressed and 97 genes were assigned to plant-pathogen interactions in ethylene pathway. Among genes that involve in ethylene biosynthesis, are MaACS2 and MaACO1. On the other hand, MaETR2, MaEIN2, MaEIL1, MaAP2/ERF and MaPR4 have important roles in ethylene signalling and defense against disease. Three triploid banana cultivars, Siem (ABB group), Nangka (AAB group), and Raja Sereh (AAB group) were used to analyse genes expression profile. RNA had isolated from pseudo stem after inoculated with BDB. Gene expression was analysed by semi quantitative PCR and ImageJ program. The result showed that expression level of MaACS2 was not significantly different between BDB injection and control in three cultivars. Expression level of MaACO1 was higher in BDB injection than control in three cultivars. In Siem and Raja Sereh, expression level of MaETR2, MaEIL1, MaAP2/ERF and MaPR4 was higher in BDB injection than control. Otherwise, there was no expression of MaEIN2 in both BDB injection and control. In Nangka, there was no expression of MaETR2, MaEIL1, and MaAP2/ERF in BDB injection, as well as there was no expression of MaEIN2 and MaAP2/ERF in control. The expression of a resistance gene, MaPR4, was higher in Siem (ABB group) than Nangka and Raja Sereh. The expression genes indicated Siem (ABB group) was more resistant than Nangka and raja Sereh.